دراسة بيانية لأنواع الخطاب في القرآن الكريم - مرزوق, الشريف (جامعة الوادي - University of Eloued, 2022)
يهدف هذا البحث إلى إبراز جوانب من الإعجاز البياني في القرآن الكريم، عند بعض القدامى والمحدثين، من خلال الشرح والتحليل لبعض الآيات القرآنية التي تناولت أنواعا من أساليب الخطاب، أبرز فيها البحث الفصاحة والبلاغة والبيان التي تفرد بها كلام الله، ثم أوضح الفوائد البيانية المستنبطة من النصوص القرآنية ، مما جعلنا نقف على سر الجمال والبيان فيها، فنؤمن بأنه القرآن الكريم المعجز بألفاظه للخلق أجمعين. كما تهدف الدراسة إلى تعميق الإيمان بوجه الإعجاز البياني من خلال التحليل والتأويل، وبيان السر الجمالي في نص الخطاب القرآني، الذي ترك آثاره في الكثير من المخاطبين. وخلص البحث إلى مجموعة من النتائج أهمها: - إن الإعجاز البياني هو أشمل وأهم وجوه الإعجاز في القرآن الكريم. - يمتاز النص القرآني بالمرونة والشمولية وفصل الخطاب. - يحوي أسلوب الخطاب في القرآن الكريم على العبر والفوائد التي من شأنها بناء حياة فاضلة. - تحوي نصوص الخطاب في القرآن على أساليب متعددة ومتنوعة، كانت ومازالت محل دراسات وبحوث Abstract : This research aims to highlight aspects of the miraculous statements in the Holy Quran, by explaining and analyzing some Quranic verses that address different types of speech styles. The research highlighted the eloquenc and the statement that God's words are unique in. The study also aims to deepen faith in the face of rhetorical miracles through analysis and interpretation, as well as to show the aesthetic secret in the text of the Qur'an discourse, which has had its impact on many receivers. The research yielded a number of results, the most important of which are: - The most important facet of the Quran is the rhetorical miracle. - The Quranic text is flexible, comprehensive and dissociative. - The style of speech in the Holy Quran contains lessons and benefits that can build a virtuous life. - The texts of the discourse in the Quran contain various and varied Methods.
Study of Types of Eloquent Speech In The Holy Quran
مقال
Keywords: الإعجاز البياني ; الخطاب القرآني ; ملامح الاعجاز القرآني ; أنواع الخطاب في القرآن; Miraculous Statements in the Holy Quran;Quranic discourse;Features of Quranic Miracle; Types of speech in the Quran.